Thyroid dyshormonogenesis is mainly caused by TPO mutations in consanguineous community. (6th May 2013) - Cangul, Hakan; Aycan, Zehra; Olivera‐Nappa, Alvaro; Saglam, Halil; Schoenmakers, Nadia A.; Boelaert, Kristien; Cetinkaya, Semra; Tarim, Omer; Bober, Ece; Darendeliler, Feyza; Bas, Veysel; Demir, Korcan; et al.
Summary Objective In this study, we aimed to investigate the genetic background of thyroid dyshormonogenesis (TDH). Context Thyroid dyshormonogenesis comprises 10–15% of all cases of congenital hypothyroidism (CH), which is the most common neonatal endocrine disorder, and might result from disruptions at any stage of thyroid hormone biosynthesis. Currently seven genes (NIS, TPO, PDS, TG, IYD, DUOX2 and DUOXA2) have been implicated in the aetiology of the disease. Design As TDH is mostly inherited in an autosomal recessive manner, we planned to conduct the study in consanguineous/multi‐case families. Patients One hundred and four patients with congenital TDH all coming from consanguineous and/or multi‐case families. Measurements Initially, we performed potential linkage analysis of cases to all seven causative‐TDH loci as well as direct sequencing of the TPO gene in cases we could not exclude linkage to this locus. In addition, in silico analyses of novel missense mutations were carried out. Results TPO had the highest potential for linkage and we identified 21 TPO mutations in 28 TDH cases showing potential linkage to this locus. Four of 10 distinct TPO mutations detected in this study were novel (A5T, Y55X, E596X, D633N). Conclusions This study underlines the importance of molecular genetic studies in diagnosis, classification and prognosis of CH and proposes a comprehensive mutation screening by new sequencing technology in all newly diagnosed primary CH cases.